How not to chaperon a lady - Heath, Virginia, 1968- (Heath, Virginia, 1968- Talk of the Beau Monde., 2021)
Griffith Philpot is charged with chaperoning Charity Brookes on her latest singing tour, but as the tour continues, their feelings begin to change toward one another.